The nexus between exchange rate fluctuations and macroeconomic variables in Nigeria - Olufemi Samuel Adegboyo (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
TThis study examined the nexus between exchange rate fluctuations and macroeconomic variables in Nigeria using annual time series data spanning from 1986 to 2017. The study employed ECMARDL and granger causality to ascertain both dynamics and directional relationship among the variables under consideration. The results showed that FDI and RGDP had positive significant effect on exchange rate fluctuations, while TOT has a positive insignificant impact on exchange rate fluctuations. Furthermore, CPI, GSPGDP, TFRESV and WCOP had negative significant impact on exchange rate fluctuations. The error correction model coefficient which is -0.704469 means that nearly 70.45 percent of any disequilibrium in exchange rate fluctuation is corrected by the selected variable within one period (one year). The findings further revealed that there is causal relationship between exchange rate and the TOT, FDI, CPI and WCOP. The implication of this is that there are directional and equilibrium relationship between exchange rate fluctuations and macroeconomic variables in Nigeria. The study therefore recommend that Government and policy makers should intensify domestic policies that accommodate or tolerate some level of (mild) inflation in order to encourage producers to expand production of goods and services, also the government should diversify the economy so that whenever there is a shock in the oil price, the shock will be less felt by the economy, and Government consumption expenditure should be carried out in a manner that it will encourage and promote investment, and increase domestic demand.